2022
DOI: 10.1002/brb3.2822
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam alleviates cellular senescence in SH‐SY5Y neuronal cells in Alzheimer's disease

Abstract: Background: Alzheimer's disease (AD) impacts the daily life of aging people. Oligomerized amyloid β (Aβ)-associated neuronal senescence is involved in the pathological mechanism of AD. Blockage of neuronal senescence has been considered an important strategy for the treatment of AD. Midazolam is a hypnotic-sedative drug with pleiotropic properties.Aims: However, the effects of Midazolam in oligomerized Aβ 1.42 -induced neurotoxicity have not been reported previously. Here, we investigate whether Midazolam poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Studies have associated additional components of this family with neuroinflammation, an early event in AD [108, 109]. TERF2 is “Repressed” in female AD patients and “Activated” in male AD patients and has been related to senescence in AD [110, 111]. Wu et al positively correlated the expression of TRF1 and TRF2 in AD patients with age and Tau protein levels in blood serum [112].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have associated additional components of this family with neuroinflammation, an early event in AD [108, 109]. TERF2 is “Repressed” in female AD patients and “Activated” in male AD patients and has been related to senescence in AD [110, 111]. Wu et al positively correlated the expression of TRF1 and TRF2 in AD patients with age and Tau protein levels in blood serum [112].…”
Section: Discussionmentioning
confidence: 99%
“…2021), neuronal cells (Wang et al . 2023), prostate cancer (Wagner et al . 2015) and in hepatocellular carcinoma (Tiwari et al .…”
Section: Catalytic Applications Of β‐Galactosidasesmentioning
confidence: 99%
“…We read with great interest the recent systematic review and meta‐analysis by Wang et al. (2023), which explored the association of hyperuricemia and gout with Alzheimer's disease. The authors observed a negative correlation between the two conditions detected by a hazard ratio of 0.69 (95% confidence interval 0.66–0.72).…”
mentioning
confidence: 99%